2010
DOI: 10.1111/j.1533-2500.2009.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Pain Management among Lithuanian Cancer Patients

Abstract: The authors believe, that to improve cancer pain management in Lithuania (1) more attention should be paid to psychological status of patients, (2) patients should be more educated about the need and consequences of opioid use for cancer pain, and (3) adherence to pain management regimens should be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 43 publications
1
15
0
2
Order By: Relevance
“…Various cognitive and educational barriers among patients may interfere with pain management by reducing adherence with treatment regimens [81,82]. Suggested components of public education include how to prevent common types of pain, how and when patients should self-treat pain, when patients should consult a doctor, what they can expect from therapy and how they can access further forms of support.…”
Section: Discussionmentioning
confidence: 99%
“…Various cognitive and educational barriers among patients may interfere with pain management by reducing adherence with treatment regimens [81,82]. Suggested components of public education include how to prevent common types of pain, how and when patients should self-treat pain, when patients should consult a doctor, what they can expect from therapy and how they can access further forms of support.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several trials have reported a positive correlation between depression and some subscales of the barrier score or the total barrier score [4, 5, 8, 31], and one [5] of these studies suggested that depression was a predictor of high barrier score to pain management. In our study population, we found that patients with depression (25 %) had more severe pain, more interfering symptoms, and poorer quality of life than did those without depression ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous patient-related [49], systematic [10, 11], and professional [12, 13] barriers are encountered in managing cancer pain. One type of patient-related barrier that may be a major contributor to poor pain control is the patient’s perspective about pain medication, which could include concerns about addiction, adverse effects, drug tolerance, the harmful effects of opioids, and distracting physicians from providing cancer treatment [5, 6, 8, 14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Although studies of analgesic adherence for cancer pain are generally lacking, existing studies have identified barriers that are multifactorial and include analgesic beliefs and concerns (Gunnarsdottir, Donovan, Serlin, Voge, & Ward, 2002; Jacobsen et al, 2010; Tzeng, Chang, Chang, & Lin, 2008), psychocognitive factors such as self-efficacy and satisfaction with pain treatment (Tzeng et al, 2008; Valeberg, Miaskowski, Hanestad, Bjordal, Moum, & Rustoen, 2008), pain and pain treatment factors (pain intensity, pain impact, pain relief, and stated need for analgesics) (Tzeng et al, 2008; Valeberg et al, 2008), and sociodemographic correlates, including age (Tzeng et al, 2008), gender, (Tzeng et al, 2008; Valeberg et al, 2008), educational level (Tzeng et al, 2008), and insurance and payment type (Bryan, De La Rosa, Hill, Amadio, & Wieder, 2008). …”
mentioning
confidence: 99%